A influência da inovação gerencial sobre uma cultura organizacional inovadora - Sousa, Isadora Farias e (2024)
Innovation has gained prominence in recent decades due to technological changes brought about by the Fourth Industrial Revolution and its impact on society's lifestyle, such that the debate on economic growth is closely linked to the pursuit of innovation. Innovation can occur in various forms, including managerial innovation, which can be defined as innovations in management or managerial practices. The aim of this study is to analyze the influence of managerial innovations on an innovative organizational culture. This is a quantitative, descriptive, and explanatory research with a positivist paradigm, in which a survey study was conducted, resulting in 200 valid questionnaires. The questionnaires were developed based on scales proposed by Lopes (2017) and Solís and Mora-Esquivel (2019), and data analysis was performed using structural equation modeling. The results indicated that managerial innovation has a significant, positive, and strong influence on nine of the ten dimensions of an innovative organizational culture, namely: external learning, teamwork, rewards, freedom of expression, task orientation, clear and shared mission, openness to change, participation, and psychological capital. However, managerial innovation did not have a significant influence on the dimension of the innovative organizational culture: flexibility regarding norms and regulations. The conclusion is that managerial innovation exerts a strong and positive influence on an innovative organizational culture. The study makes a theoretical contribution by presenting a new relationship between managerial innovation and innovative organizational culture, with relationships that have not yet been tested in the literature, and by proposing a model that makes managerial innovation tangible and relates it to another construct, which is innovative organizational culture. The social contribution of the study is to present the workers' perceptions about managerial innovation, and the empirical contribution of this research lies in showing that managerial innovation can be a tool for transforming organizational culture and, consequently, for the development of people.